Mapeamento de áreas de conflitos ambiental no estuário do rio Apodi/Mossoró - Souza, Italo Bruno Fonseca de (Universidade Federal Rural do Semi-Árido, 2019)
The northern coast of Rio Grande do Norte is the stage of a typical situation of conflict between an important economic sector for the region and one of the most productive coastal ecosystems. Knowing this, this work aims at mapping such areas of conflict that involve the occupation of mangrove areas by the salt flats, as well as analyzing the main legal instruments related to the theme. The studies were carried out in the Apodi / Mossoró river estuary, which is approximately 43 km long, extending from the municipality of Mossoró to its mouth in the Atlantic Ocean between the municipalities of Grossos and Areia Branca. For legal analysis of the conflict, extensive research was carried out on technical and legal documents related to mangroves and the production of sea salt. The Permanent Preservation Area was determined based on the New Forest Code, with APP margins varying between 100 and 200 m. The importance of producing sea salt for the country's sanitary safety as well as the chemical industry is well known, with the Permanent Preservation Areas of the Apodi / Mossoró estuary mostly being converted into production areas for this mineral. Even if the current legislation does not consider this irregular occupation, thus discharging the existence of legal conflict, the occupation of these areas reduces the production potential of the ecosystem and negatively interferes in its capacity to provide ecosystem services, implying damage to the ecosystem. local community.
Artigo Acadêmico
Keywords: Área de preservação permanente; Conflito legal; Estuário; Código florestal; Industria salineira; Permanent conservation area; Legal conflict estuary; Forest code; Saline industry; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA